The impact of developmental stress on the functioning and vulnerability of CNS neurons - Pienaar, Ilse-Sanet (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Biomedical Sciences. Medical Physiology))--Stellenbosch University, 2008.